Variation of the Labor Force Distribution according to the Economic Activity of the Population of Anbar Province for the Period 1987 - 2011 - مصطفى عبد الله السويدي عذراء عبد حمد (College of Education for Women, 2019)
This study deals with the Spatial and Periodical Variation of the Economical Activities for the Population of Al - Anbar Province on the level of districts , according to the Population Computation for the period 1987 and 1997 and the results of determinations and numberings for the year of 2011 . This study depends on the Details Classifications of the 17th Activities for 1997 and 2011 beside the Triple Classification of the Economical Activities for the three study years . The study proves that there is a spatial and periodical variation on the level of study area , and that's because of many factors , one of the most important of them was the distribution of economical siege, as well as the weakness of the security conditions , where the workers in the agricultural activity is increased for 1997 , and then decreased in 2011 , with the increasing in industrial field in most of districts in 1997 and 2011 , and that indicates to the decreasing in Agricultural lands with the increasing in population , and the presence of rarefaction in the work of industrial plants between their work and stoppage because of the security conditions during the U.S. occupation and the accompanying of conditions that influenced the work of such plants and thus its employees.